Clinical and Laboratory Characteristics of Triple-Negative Breast Cancer: A Study on a Sample of Tishreen University Hospital Patients - كناج دعاء (Latakia University Journal -Medical Sciences Series, 2021)
Background: Breast cancer is a common cancer, and considered a heterogeneous subtype that includes a group of diseases. Triple negative breast cancer is characterized by aggressive behavior and bad prognosis. Methods: We reviewed the clinical files and pathology reports of 100 patients who had triple negative breast cancer during the period 2013-2018 at Tishreen University Hospital. We have collected the information about (age at diagnosis, histological subtype of tumor, tumor grade, tumor size, tumor stage, number of involved lymph nodes, and value of CA15-3) for each patient. Results: 85% of patients were at age (40 or more) at diagnosis, IDC (84%), grade2 (52%), tumor size T2 (72%), stage 2 (63%), negative lymph nodes N0 (41%), normal value of CA15-3 (83%). We found no relationship between age at diagnosis and laboratory characteristics of triple negative breast cancer patients. Conclusion: Triple negative breast cancer is more likely to happen at older ages, commonly with grade 2 tumor.